The Effect of Murottal Therapy in Decreasing Depression of Patients Undergoing Hemodialysis - Desi Ariyana Rahayu; Tri Nur Hidayati; Tsulis Ahmad Imam (Universitas Muhammadiyah Semarang, 2018)
Background: Hemodialysis can be performed 1 to 3 times a week according to the degree of kidney damage and takes 3 - 5 hours each time. The activity done regularly and continuously throughout life and cause negative effects such as discomfort, decreased quality of life including physical health, psychological, spiritual, and socioeconomic status. The psychological impacts include anxiety, stress and depression. This research aimed to analyze the influence of Murottal therapy on depression of patients undergoing hemodialysis.Method: The research used quasi experimental method with one group pretest-posttest design. The sampling was done by purposive sampling. Data collection used DASS questionnaires. Data was analyzed using T-test and Wilcoxon test. Result: It was found that depression levels were decreased after the given of Murottal therapy. There were 26 respondents performed normal condition (86.7%) and 4 respondents performed mild depression (13.3%).Analyzis: Murottal therapy decreased the depression level on patients undergoing hemodialysis which showed by the T-test correlation with p-value 0.000 (<0.05).Conclusion: Murottal therapy decreased the depression levels of patients undergoing hemodialysisKeywords: Hemodialysis, depression, Murottal tehrapyLiterature: 60 (2005-2017)